2015
DOI: 10.1111/nan.12134
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C is differentially involved in multiple system atrophy phenotypes

Abstract: CysC changes are differentially present in the parkinsonian and cerebellar forms of MSA and may play an important role in the pathogenesis of this neurodegenerative condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
1
5
0
1
Order By: Relevance
“…Both levels of Cys C in serum or CSF of AD patients have been shown to be lower 43 , 48 , 49 , and the Cys C levels in CSF is strong positively correlation with alteration of both tau and Aβ 42 levels in CSF 43 . High mRNA levels of Cys C were found in caudate nuclei and cerebella of MSA patients brain 50 and similar results were observed in the vitro and vivo model of Parkinson's disease 51 , 52 . Like AD, the levels of Cys C in CSF are seemingly decreased during disease progression in ALS patients and the reduced Cys C is negatively correlated with survival time 26 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Both levels of Cys C in serum or CSF of AD patients have been shown to be lower 43 , 48 , 49 , and the Cys C levels in CSF is strong positively correlation with alteration of both tau and Aβ 42 levels in CSF 43 . High mRNA levels of Cys C were found in caudate nuclei and cerebella of MSA patients brain 50 and similar results were observed in the vitro and vivo model of Parkinson's disease 51 , 52 . Like AD, the levels of Cys C in CSF are seemingly decreased during disease progression in ALS patients and the reduced Cys C is negatively correlated with survival time 26 .…”
Section: Discussionsupporting
confidence: 83%
“…Several studies of relevant NDDs showed the reduced levels of Cys C in CSF or the increased expression of Cys C in degenerative neurons 18 , 48 , 49 , 50 , 51 . Both levels of Cys C in serum or CSF of AD patients have been shown to be lower 43 , 48 , 49 , and the Cys C levels in CSF is strong positively correlation with alteration of both tau and Aβ 42 levels in CSF 43 .…”
Section: Discussionmentioning
confidence: 99%
“…In a former study, Urbizu et al (2015) confirmed that the transcription of Cys-C was differentially expressed in different MSA phenotypes. The Cys-C gene (CST3) B-haplotype was significantly associated with MSA-P, while the higher expression of CST3 were found in the caudate nuclei of MSA-P and in the cerebellum of MSA-C.…”
Section: Discussionmentioning
confidence: 68%
“…Monoclonal and polyclonal antibodies against CPE were obtained from BD Biosciences (610758, BD Transduction Laboratories, San Jose, CA) and GeneTex (GTX23533, GeneTex Inc), respectively [ 45 , 46 ]. Polyclonal antibodies against CysC (ABC20) [ 47 ] and monoclonal antibodies against GFAP (MAB3402) were obtained from Millipore Iberica (Madrid, Spain). Monoclonal and polyclonal antibodies against CHMP2B (MAB7509) and CK1δ (AF4568) were purchased from R&D Systems (Minneapolis, MN).…”
Section: Methodsmentioning
confidence: 99%